Anti-Inflammatory Drug Design Using a Molecular Hybridization Approach - Jean Leandro dos Santos; Man Chin Chung; Ednir Oliveira Vizioli; Priscila Longhin Bosquesi; Thais Regina Ferreira Melo (MDPI AG, 2011)
The design of new drugs with better physiochemical properties, adequate absorption, distribution, metabolism, and excretion, effective pharmacologic potency and lacking toxicity remains is a challenge. Inflammation is the initial trigger of several different diseases, such as Alzheimer's disease, asthma, atherosclerosis, colitis, rheumatoid arthritis, depression, cancer; and disorders such as obesity and sexual dysfunction. Although inflammation is not the direct cause of these disorders, inflammatory processes often increase related pain and suffering. New anti-inflammatory drugs developed using molecular hybridization techniques to obtain multiple-ligand drugs can act at one or multiple targets, allowing for synergic action and minimizing toxicity. This work is a review of new anti-inflammatory drugs developed using the molecular modification approach.